Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/v13112291
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Composition of Vector Abundance in Hanoi City, Vietnam: Association with Livestock Keeping and Flavivirus Detection

Abstract: Background: Dengue virus and Japanese encephalitis virus are two common flaviviruses that are spread widely by Aedes and Culex mosquitoes. Livestock keeping is vital for cities; however, it can pose the risk of increasing the mosquito population. Our study explored how livestock keeping in and around a large city is associated with the presence of mosquitoes and the risk of them spreading flaviviruses. Methods: An entomological study was conducted in 6 districts with 233 households with livestock, and 280 hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Knowledge of larval habitat characteristics in an area and its impacts on mosquito diversity, abundance, and distribution is critical for developing integrated vector control strategies and mitigating future outbreaks of mosquito-borne diseases. The current study has reported a higher number of mosquito species than previous studies in Ha Noi (Pham, 2015;Nguyen et al, 2021). Moreover, it is worth noting that there were five new records for urban areas of Ha Noi city including An.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Knowledge of larval habitat characteristics in an area and its impacts on mosquito diversity, abundance, and distribution is critical for developing integrated vector control strategies and mitigating future outbreaks of mosquito-borne diseases. The current study has reported a higher number of mosquito species than previous studies in Ha Noi (Pham, 2015;Nguyen et al, 2021). Moreover, it is worth noting that there were five new records for urban areas of Ha Noi city including An.…”
Section: Discussionsupporting
confidence: 41%
“…Particularly, a study investigated insect fauna in residential areas in Ha Noi has reported only a few mosquito species, including Culex quinquefasciatus, Culex tritaenyorhynchus, Aedes aegypti, Aedes albopictus, and Anopheles sinensis (Pham, 2015). The study by Nguyen et al (2021) aimed to assess the effects of livestock on the abundance of mosquitoes in urban households in Ha Noi has reported 10 species including Ae. aegypti, Ae.…”
Section: Introductionmentioning
confidence: 99%
“…The etiological agent of one of the most problematic mosquito-borne diseases of humans, dengue virus (DENV) causes around 100 million symptomatic cases each year worldwide, approximately 70% of which occur in Asia [11]. In 2013, the global economic burden of dengue was estimated at US $8.9 billion [12], a figure which will have grown considerably in the intervening decade. In tropical and subtropical countries, dengue is increasingly prevalent in cities and suburbs [11,13], compared to rural areas, as the predominant Aedes aegypti (Ae.…”
Section: Dengue Virus Transmissionmentioning
confidence: 99%
“…Mosquitoes are key players in the spread of vector-borne diseases, such as Japanese encephalitis and West Nile fever, representing a significant global health concern. Vector-borne viruses collectively account for close to 700,000 deaths each year and are rapidly emerging as prominent threats to local populations 1 , 2 . Factors that may change vector dynamics and can alter vector abundance, such as urbanization, changes in land-use, deforestation, and climate change contribute to the escalating prevalence of mosquito-borne illness worldwide 3 .Understandng the abundance and dynamics of mosquito vectors is crucial for assessing the risks of arboviral diseases and anticipating future outbreaks 4 6 , and to enable timely implementation of control measures to mitigate the risk of human infection 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Mosquito-borne diseases are highly prevalent in South-East Asia, including Vietnam 3 , and Japanese Encephalitis virus (JEV), dengue virus (DENV), Zika virus (ZIKV), and chikungunya virus (CHIKV) are examples of viruses endemic in Vietnam 2 , 3 .JEV is a highly pathogenic mosquito-borne flavivirus, that causes encephalitis in humans and horses in tropical and temperate regions of Asia 7 , 8 . Pigs act as amplifying hosts and can be affected by the virus, mainly resulting in abortions and neonatal deaths 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%